Performance of CT Angiography on a Mobile Stroke Treatment Unit: Implications for Triage. Issue 4 (30th March 2016) - John, Seby; Stock, Sarah; Masaryk, Thomas; Bauer, Andrew; Cerejo, Russell; Uchino, Ken; Winners, Stacey; Rasmussen, Peter; Hussain, Muhammad S.
ABSTRACT: BACKGROUND: There is a strong inverse relationship between outcome in patients with acute ischemic stroke from emergent large vessel occlusion (ELVO), and time to reperfusion from intra‐arterial therapy. Delay in transferring patients to thrombectomy‐capable centers is currently a major limitation. The mobile stroke unit (MSU) concept with onboard portable computed tomography (CT) scanner enables rapid performance of CT angiography (CTA) of the intracranial vessels to detect ELVO in the field, and allows for rapid triage of patients to interventional‐capable centers. METHODS: Our institution implemented a mobile stroke treatment unit (MSTU) program that started on July 2014, and CTA capability was added on April 2015. The eligibility criteria, equipment, and method of CTA imaging are described. We report the first case of CTA being performed in the field in the United States to aid in triage of ELVO patients. RESULTS: MSTU was dispatched for reported new onset of right hemiparesis in a patient. Teleneurological assessment detected findings consistent with a severe left middle cerebral artery (MCA) syndrome. Noncontrast CT head revealed left lenticulostriate hypoattenuation. A CTA was performed subsequently on the MSTU that showed an MCA cutoff. Based on these findings, patient was immediately transferred to the main hospital with neurointerventional capability, where he underwent successful recanalization with improvement in symptoms. CONCLUSION: CTA is possible on an MSTU, enabling rapid detection and triage of ELVO cases directly to thrombectomy‐capable centers, which significantly reduces time to endovascular treatment.